A Student-Initiated, Integrated Pharmacotherapeutics Learner-Centered Course - Shawn Hopman; Nicholas G. Popovich (University of Minnesota Libraries Publishing, 2015)
Objective: To evaluate a learner-centered, elective course complementing pharmacotherapeutic instruction. Design: A one credit-hour elective as developed. Enrolled students were responsible for article selection and to lead in-class discussions. A content-validated discussant rubric was use to peer review each discussant. Assessment: Enrolled students kept current on the literature and nurtured an obligation to themselves and their peers to be prepared on a weekly basis to discuss the selected article. Discussion demonstrated varied opinions and provided ample opportunity for students to use technical/clinical language. Also, the course allowed for thinking at a higher level, discussing complex ideas/issues, and developing oral communication skills. Conclusions: This learner-centered approach allowed the enrolled students to take ownership of their learning and complement their learning from the traditional mode of learning in two pharmacotherapeutic courses. It encouraged the students to investigate the clinical literature as a means to complement and enhance their knowledge.   Type: Note